Kepemilikan Umum dalam Islam - Jajuli, Sulaeman (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
Among the fundamental difference between the Islamic economic system by the capitalist and socialist economic system is the issue of ownership. In a capitalist economic system of individual ownership there is no limit so that everyone is given the freedom to have a variety of natural resources there is no view of public interest. While the Socialist economic system negates ownership for individuals so that all forms of production and sources of income become the property of the state or the entire community. How to ownership in Islam? Islam is a rule (role) that is consistent with human life and nature, so that ownership rights in Islam includes the right to private property, public and state. In other words, Islam adopts multype ownership (multiple ownership type). It is as a middle ground for people in possession of the problems they face. Humans would need something that can be used for personal interests, so there are some things that are needed by everyone so that the object should not be owned by individuals. In addition, some natural resources can not be owned by individuals or private, semisasl gold mine in an area, then the government has the right to own and manage it for the benefit of all citizens.